Service Performance Analysis Using Fault Tree Analysis (FTA) at the Investment and One-Stop Integrated Services Office (Case Study in Kampar Regency) - Muliani, Kurnia; Azriadi, Emon; Musridho, R. Joko (Journal of Engineering Science and Technology Management (JES-TM), 2025)
High-quality public service performance is highly needed. However, the Investment and One- Stop Integrated Services Agency (DPMPTSP) of Kampar Regency faces challenges in the form of low service speed, as seen from the results of the 2023 Community Satisfaction Survey (SKM). This study aims to analyze the causes of delays in environmental permit services at the DPMPTSP of Kampar Regency using the Fault Tree Analysis (FTA) method. FTA is used to identify the root causes of failure and the logical relationship between the existing factors. Data was collected through interviews with officials from the DPMPTSP and the Environmental Agency (DLH) of Kampar Regency, as well as document studies. The results of the study show that the delays are caused by three main factors: (1) business actor factors, (2) Technical Regional Apparatus Organization (OPD) factors, and (3) internal DPMPTSP factors. The FTA analysis highlights that business actor factors, such as a lack of knowledge and slow feedback, are the most dominant root cause of the problem. Increased collaboration between business actors and relevant OPDs is needed to accelerate the permit process and improve community satisfaction.